Análise exploratória do perfil de voláteis em cervejas Pilsen artesanais e industriais utilizando cromatografia a gás por ionização em chama e espectrômetro de massas - Stephanie Vertelo Porto (2023)
The quality of beer is usually associated with its sensorial aspects, such as flavor and aroma. These characteristics are influenced by the volatile compounds produced during the beer production process and are mainly synthesized by yeast. This work aimed to carry out an exploratory analysis of industrial and craft Pilsner beers using the headspace solid-phase microextraction technique (HS-SPME) with a polyacrylate fiber (PA) with subsequent analysis by gas chromatography coupled to a mass spectrometer (GC–MS). Initially, a Box-Behnken experimental design (BBD) and response surface methodology were used to evaluate the extraction parameters regarding the signals obtained for three classes of analytes, namely alcohols (higher and monoterpene), esters, and carboxylic acids. The optimal conditions were an extraction time of 40 min, an extraction temperature of 40 °C, and a sample volume of 4 mL. A total of 22 samples, 11 industrial beers and 11 craft beers, were analyzed using the proposed method, in duplicate. The analysis of results was performed using multivariate methods, such as principal component analysis (PCA) and hierarchical cluster analysis (HCA). The clusters obtained made it possible to group the samples and investigate the differences and similarities between craft and industrial beers concerning the analytes evaluated.